Heteroatom Doped Amorphous/Crystalline Ruthenium Oxide Nanocages as a Remarkable Bifunctional Electrocatalyst for Overall Water Splitting. Issue 11 (17th January 2023) - Liu, Dandan; Wu, Zeyi; Liu, Jiajia; Gu, Hongfei; Li, You; Li, Xueyan; Liu, Shan; Liu, Shange; Zhang, Jiatao
Abstract: Developing robust and highly active bifunctional electrocatalysts for overall water splitting is critical for efficient sustainable energy conversion. Herein, heteroatom‐doped amorphous/crystalline ruthenium oxide‐based hollow nanocages (M‐ZnRuOx (MCo, Ni, Fe)) through delicate control of composition and structure is reported. Among as‐synthesized M‐ZnRuOx nanocages, Co‐ZnRuOx nanocages deliver an ultralow overpotential of 17 mV at 10 mA cm −2 and a small Tafel slope of 21.61 mV dec −1 for hydrogen evolution reaction (HER), surpassing the commercial Pt/C catalyst, which benefits from the synergistic coupling effect between electron regulation induced by Co doping and amorphous/crystalline heterophase structure. Moreover, the incorporation of Co prevents Ru from over‐oxidation under oxygen evolution reaction (OER) operation, realizing the leap from a monofunctional to multifunctional electrocatalyst and then Co‐ZnRuOx nanocages exhibit remarkable OER catalytic activity as well as overall water splitting performance. Combining theory calculations with spectroscopy analysis reveal that Co is not only the optimal active site, increasing the number of exposed active sites while also boosting the long‐term durability of catalyst by modulating the electronic structure of Ru atoms. This work opens a considerable avenue to design highly active and durable Ru‐based electrocatalysts. Abstract : Heteroatom Co doped amorphous/crystalline Co‐ZnRuOx nanocages are obtained by a facile ion‐exchange and subsequent annealing procedure, Co doping enables ZnRuOx nanocages to transition from a monofunctional electrocatalyst to multifunctional electrocatalyst for overall water splitting in alkaline media. The synergistic coupling effect between electron regulation induced by Co atoms and heterophase structure is evidenced by spectroscopy analysis and theory calculations.